Nilai-nilai Khazanah Kearifan Lokal dalam Pengembangan Pendidikan Islam di Lingkungan Pesantren - Aceng Badruzzaman; Muhammad Najamuddin Dwi Miharja (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Islamic education is referred to as a system and method for improving the quality of human life which basically aims to develop true Muslim individuals by developing each person's physical and spiritual potential. This research aims to identify and analyze local wisdom values ​​that can be integrated in the development of Islamic education in the Islamic boarding school environment. Local wisdom is cultural wealth that contains noble values, which, if applied in Islamic education, can enrich and strengthen the character of students. Using a qualitative approach with a case study method, this research examines educational practices in several Islamic boarding schools that have succeeded in integrating local wisdom in their curriculum. The research results show that local wisdom values, such as mutual cooperation, tolerance and respect for nature, have high relevance to the basic principles of Islam. The implementation of these values ​​not only deepens understanding of religion, but also shapes the attitudes and behavior of students who are more civilized and broad-minded. The conclusions of this research emphasize the importance of developing an adaptive and contextual curriculum, which is able to accommodate local wisdom values ​​to improve the quality of education in Islamic boarding schools. It is hoped that these findings can become a reference for Islamic boarding school managers in designing holistic and integrative education programs.